Global Imbalances and Financial Stability - Xafa, Miranda (IMF Working Papers; Working Paper ;, 2007)
This paper discusses two opposing views on global imbalances: The "traditional view", which regards the imbalances as a threat to global economic and financial stability, and the "new paradigm" view, which considers that they are the natural consequence of economic and financial globalization. In terms of their policy implications, the traditional view focuses on monetary and fiscal policy decisions in the United States that need to be urgently reversed to avoid an abrupt unwinding of the imbalances involving a sell-off of dollar assets, a sharp increase in U.S. interest rates, and a hard landing for the global economy. By contrast, the new paradigm view considers that the imbalances will be resolved smoothly through the normal functioning of markets. The paper argues that an abrupt unwinding of imbalances is highly unlikely and advances a number of arguments in support of the new paradigm view.